Cortical activation characteristics during different swallowing tasks in post-stroke patients: a functional near-infrared spectroscopy study - Guo, Meng; Tang, You; Liu, Wenjing; Zhang, Yuxuan; Sun, Zihao; Wan, Chunxiao (Frontiers in Neurology, 2026)
ObjectiveThis study employed functional near-infrared spectroscopy (fNIRS) to investigate cortical activation patterns in post-stroke dysphagia (PSD) patients compared with non-dysphagic patients during specific swallowing tasks.MethodsTwenty-nine patients with supratentorial stroke were recruited and divided into a dysphagic group (n = 14) and a control group (n = 15). Brain activity was monitored using fNIRS during single swallowing task (SST), continuous swallowing task (CST), and video-continuous swallowing dual-task test (DTT). Activation patterns were analyzed within and between groups using the general linear model (GLM) and block-average hemodynamic analysis.ResultsIn the dysphagia group, during the SST, activation was observed in the R-FPA, bilateral PSMC, and L-DLPFC (p < 0.05). During the CST, activation was observed in the R-PSMC (p < 0.05), while during the DTT, activation was limited to the L-S1 (p < 0.05). Intragroup comparisons showed that only the R-FPA exhibited significantly greater activation during the DTT compared to the SST (p < 0.05). In the control group, during the SST, activation was observed in the R-S1, bilateral FPA, and R-PSMC (p < 0.05). During the CST, activation was observed in the R-IFG and L-PSMC (p < 0.05). During the DTT, widespread activation was observed in the R-IFG, L-DLPFC, L-S1, L-FPA, L-PSMC and R-M1 (p < 0.05). Intragroup comparisons revealed that activation levels across multiple regions, including bilateral FPA, R-DLPFC, and L-PSMC during the CST, and bilateral S1, bilateral DLPFC, bilateral PSMC, and L-FPA during the DTT, were significantly higher than during the SST (p < 0.05). Block-average analysis revealed that the dysphagic group exhibited significantly higher activation in motor and sensory cortical regions during the SST, reduced activation in prefrontal areas during the CST, and limited cortical modulation during the DTT compared to controls (p < 0.05).ConclusionThis fNIRS study revealed distinct cortical activation patterns between post-stroke patients with and without dysphagia. PSD patients demonstrated compensatory hyperactivation in motor-related cortical regions during simple tasks, but exhibited limited modulation capacity under more demanding conditions. In contrast, non-dysphagic patients showed widespread, coordinated cortical activation that scaled with task complexity. These findings suggest that PSD is associated with impaired functional reorganization of cortical swallowing networks.Clinical trial registrationhttps://www.chictr.org.cn/, identifier ChiCTR2500098164.